Influence of the Coupling South Atlantic Convergence Zone-El Nino-Southern Oscillation (SACZ-ENSO) on the Projected Precipitation Changes over the Central Andes - Sulca, Juan C. (2021)
Juan Sulca was funded by Peruvian PPR068 program Reduccion de vulnerabilidad y atencion de emergencias por desastres. The work was performed using computational resources, HPC-Linux-Cluster, from Laboratorio de Dinamica de Fluidos Geofisicos Computacionales at Instituto Geofisico del Peru (grants 101-2014-FONDECYT). R. P. da Rocha thanks to CNPq-Brazil (#304949/2018-3 and 430314/2018-3). Moreover, the authors thank Enciso for his help with the production of some figures. We are very grateful to three anonymous reviewers who provided us with valuable comments, which helped us to advance our results significantly and to improve the paper.